The dynamics of business cycles stylized facts using quarterly data for six industrialized countries - Βαρελάς, Ερωτόκριτος Γ. (SPOUDAI Journal of Economics and Business, 2004)
This paper examines the empirical evidence concerning the identification of cycles of the aggregate industrial production, prices and money for six OECD countries using quarterly data. We used Spectral Analysis (univariate and multivariate). An interesting result is that the monetary aggregates are procyclical. JEL Classification: E32, E10